Relative Price Skewness and Inflation: A Structural VAR Framework - Attila Rátfai (Hungarian Academy of Sciences, Institute of Economics, 2001)
This study evaluates the empirical significance of idiosyncratic pricing shocks in inflation dynamics. To this end, using store-level price data for a selected group of products and employing identification schemes dictated by (S,s) pricing theory, product-level Structural Vector Autoregressions comprised of inflation and relative price skewness are estimated. Robustly to alternative identification assumptions, definitions of the relative price and measures of asymmetry in relative price distributions, idiosyncratic shocks tend to explain about 25 to 30 percent of the forecast error variance in inflation rates at the 12-month horizon. They also lead to substantial build-up in inflation after about 3 to 5 months following the initial disturbance.
Keywords: 330; inflation dynamics (S; s) princing models; structural VAR analysis